1996
DOI: 10.1159/000159184
|View full text |Cite
|
Sign up to set email alerts
|

Diminishment of Contractions Associated with Depolarization-Evoked Activation of Ca<sup>2+</sup> Channels in Diabetic Rat Aorta

Abstract: Alterations in contractile responses of aortic rings mediated by activation of Ca2+ channels were investigated in rats with streptozotocin-induced diabetes. Eight to 12 weeks of diabetes resulted in a marked decrease in the contractile response of aortic rings to high K+. In contrast, diabetic aortas exhibited significantly greater contractions in response to noradrenaline compared to age-matched controls. In the presence of 15 ml K+, the Ca2+ channel agonist Bay K 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The contractile response evoked by K ϩ depolarization has been found to be diminished (4,8), increased (26), or not influenced (1,14) in diabetic blood vessels, depending on the experimental models, vascular tissue types, and the duration of diabetes. For instance, the contraction and 45 Ca uptake of aortic tissues induced by high K ϩ were both suppressed in STZ-induced 2-to 3-mo diabetic rats (7). These results suggested the abnormalities of VDCC in diabetic vascular SMCs.…”
Section: Discussionmentioning
confidence: 73%
“…The contractile response evoked by K ϩ depolarization has been found to be diminished (4,8), increased (26), or not influenced (1,14) in diabetic blood vessels, depending on the experimental models, vascular tissue types, and the duration of diabetes. For instance, the contraction and 45 Ca uptake of aortic tissues induced by high K ϩ were both suppressed in STZ-induced 2-to 3-mo diabetic rats (7). These results suggested the abnormalities of VDCC in diabetic vascular SMCs.…”
Section: Discussionmentioning
confidence: 73%
“…In other smooth muscles mainly studied in diabetic animals, both increased and decreased agonist responses are reported (e.g. [34–36]) and no consistent mechanism has been identified.Our data with high K + stimulation showed a significant decrease in amplitude of force and Ca rise in diabetic samples. There is no consistency in the reported effects of high K+ on other smooth muscle preparations from diabetic tissues, with similar findings to ours reported by some [3638], but no change or increase by others [20, 39].…”
Section: Discussionmentioning
confidence: 99%
“…[34–36]) and no consistent mechanism has been identified.Our data with high K + stimulation showed a significant decrease in amplitude of force and Ca rise in diabetic samples. There is no consistency in the reported effects of high K+ on other smooth muscle preparations from diabetic tissues, with similar findings to ours reported by some [3638], but no change or increase by others [20, 39]. Our data are consistent with those of Wang et al [40], who also found decreased L-type Ca 2+ current density discussed below, but our data could also be due to decreased channel expression and altered channel kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that KCl depolarisation-induced changes in [Ca 2+ ] i and contractions are diminished in both macrovascular and microvascular smooth muscle cells from diabetic rats [27,28,29,30,31] and this is thought to occur through a reduction in the density of voltage-dependent L-type Ca 2+ channels [32] (VDCC). In our study, the action of high K + was maintained in the retinal MVSM cells from diabetic rats suggesting that neither the VDCCs themselves nor their activation require- PKC activation (PMA).…”
Section: Discussionmentioning
confidence: 99%